Do pre-schoolers with high touchscreen use show executive function differences?. (February 2023) - Portugal, Ana Maria; Hendry, Alexandra; Smith, Tim J.; Bedford, Rachael
Abstract: The recent increase in children's use of digital media, both TV and touchscreen devices (e.g., tablets and smartphones), has been associated with developmental differences in Executive Functions (EF). It has been hypothesised that early exposure to attention-commanding and contingent stimulation provided by touchscreens may increase reliance on bottom-up perceptual processes and limit the opportunity for practice of voluntary (i.e., top-down) attention leading to differences in EF. This study tests the concurrent and longitudinal associations between touchscreen use (high use, HU ≥ 15 min/day; low use, LU < 15 min/day), and two components of EF (working-memory/cognitive-flexibility, and impulse/self-control), building explicitly on recent developmental models that point to a bidimensional structure of EF during toddlerhood and pre-school years. A longitudinal sample of 46 3.5-year-olds (23 girls) was tested on a battery of lab-based measures and matched at 12 months on a range of background variables including temperament. Touchscreen HU showed significantly reduced performance in lab-based Working Memory/Cognitive Flexibility, although this became non-significant when controlling for background TV. Impulse/Self-control was not significantly associated with touchscreen use but was negatively associated with non-child-directed television. Our results provide partial support for the hypothesis that using touchscreen devices might reduce capacity for top-down behaviour control, and indicate that broader media environment may be implicated in early executive function development. However, it may also be the case that individuals who are predisposed towards exogenous stimulation are more drawn to screen use. Future studies are needed to replicate findings, demonstrate causality, and investigate bidirectionality. Highlights: This study tested Executive Functions and touchscreen use in 3.5-year-olds. High touchscreen users had reduced Working Memory/Cognitive Flexibility. Impulse/Self-control seemed to be related to the broader family media environment. Future work should investigate causality and different types of platforms and use.